Materials from excavations of Fioletovo - Gevorgyan, Aram; Azizyan, Anna (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The Fioletovo settlement is located on the outskirts of the homonymous village in the province of Lori. The coordinates of the settlement are: N 40 71 68 71. E 44 73 55 34: The Aghstev river flows right from the north foot of the site. The locals call it ‘Fortress’. The settlement is located in a region with a large number of mineral ores. Тhese mineral resources have been used by the society since ancient times. In 1955, the first excavations were carried out within the area of the site by H. Mnatsakanyan, and then, in 1999 by A. Gevorgyan. As a result of the excavations, both complete and fragmentary pottery and various lithic tools were unearthed.